Confusão de consoantes e geometria de traços - Lílian Marinho dos Santos (2012)
The speech perception directly interferes with effective communication of day to day and is dependent on the proper integration of auditory skills for the effective recognition of consonants in quiet and in noise. A representation of speech sounds by means of distinctive features is the geometry of feature theory, which proposes a hierarchical organization of sounds. The objectives of this thesis were a) characterize the performance of adult subjects in the tasks of perception of consonants in different types of noise in the same context, b) assess the association between the theory of feature geometry and the perception of consonants, c) and the distinctive features, test whether the more distinctive features consonants share, the shorter the distance between the sounds, that is, the more confused they are. Material and Methods: This is an experimental study with repeated measures. The collection of survey data was divided into two steps: 1) Preliminary, whose purpose was to select the sample to subjects with peripheral hearing and auditory processing within the normal range, 2) Assessment of the perception of consonants, whose goal was check the confusion of consonants [p], [t], [d], [k], [f], [v], [] e [] followed by the vowel [a], amid the white noise and party noise at signal-noise ratio of 0 and +5dB (NS). Results: In white noise, at signal noise ratio of 0 and +5dB (NS), were found in more confusion: [f] [p], [] [k] e [] []. In the noise party, at signal noise ratio of 0 and + 5dB (NS) were found more confusion: [f] [p], [v] [p] e [v] [f] e [t] [d]. For both white noise and for noise festival, the confusion was more frequently found between [f] and [p]. We observed a different pattern of confusion regarding the noise white and party, where the percentage of errors in most cases was higher in the noise party. As for distinctive features, it was observed that the more distinctive features of consonants share, the more confused they are. A more confusion occurs at the bottom of the hierarchy tree of features, in node depending point; The difference among the groups regarding the types of noise are difficult to explain only from the geometry of features. Conclusion: We conclude that the noise white and noise party are directly affect the perception of consonants differently. Geometry of features does not fully explain the confusion of consonants found in the noise, but his prediction was verified that the more distinctive features pairs of consonants share, the more confused they are.